An abortive renaissance: catholic modernists in Sussex - Vidler, Alexander Roper (Studies in church history, 1977)
Storrington in Sussex, at the beginning of this century, was described as ‘a quiet, peaceful village.’ Although in the intervening period its population has more than doubled, it is still known as a village and has retained much of that agreeable character. In 1909 it suddenly became the centre of an ecclesiastical cause célèbre that attracted international attention. Anyone who was in Storrington on 21 July in that year could have witnessed an extraordinary funeral.It was the burial of a Roman catholic priest. The mourners, who numbered about forty, assembled in the garden of the house in the middle of the village where the priest had died and walked from there in silence to a grave that had been prepared in the anglican or parish churchyard. There was no requiem or formal funeral service, but prayers were said and an address was given by an unrobed priest who was in fact a Frenchman, though that might not have been evident since he was fluent in English. He said that he spoke in the name of many French, Italian and German friends, for father George Tyrrell, whose funeral it was, had become well-known in those countries and in others too. He was one of the most conspicuous representatives of what is known to historians as the modernist movement in the Roman catholic church and of what may be described as an abortive renaissance.